2022
DOI: 10.3389/fonc.2022.1042196
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic reprogramming by miRNAs in the tumor microenvironment: Focused on immunometabolism

Abstract: MicroRNAs (miRNAs) are emerging as a significant modulator of immunity, and their abnormal expression/activity has been linked to numerous human disorders, such as cancer. It is now known that miRNAs potentially modulate the production of several metabolic processes in tumor-associated immune cells and indirectly via different metabolic enzymes that affect tumor-associated signaling cascades. For instance, Let-7 has been identified as a crucial modulator for the long-lasting survival of CD8+ T cells (naive phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 262 publications
(298 reference statements)
0
5
0
Order By: Relevance
“…One of the most commonly cited prognostic factors which has been recently investigated in patients suffering from malignant diseases is represented by the inflammatory status of each patient. Therefore, it has been widely demonstrated that molecular and genetic mechanisms of tumorigenesis as well as tumour progression and angiogenesis are strongly influenced by the immune status of the host as well as by different homeostatic mechanisms [13][14][15][16][17]. In this respect, it has been demonstrated that platelets seem to play a central role in promoting tumoral cells' growth, dissemination and colonization determining the apparition of metastatic deposits, especially through the process of degranulation and the release of proinflammatory cytokines (such as interleukin 6) and Meanwhile, when studying the possible correlation between BRCA status, inflammatory markers and disease-free and overall survival, we observed that BRCA-mutated patients with SII ≥ 841,000 and those with higher NLR values had significantly worse DFS compared to patients with SII < 841,000 and with lower NLR values.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most commonly cited prognostic factors which has been recently investigated in patients suffering from malignant diseases is represented by the inflammatory status of each patient. Therefore, it has been widely demonstrated that molecular and genetic mechanisms of tumorigenesis as well as tumour progression and angiogenesis are strongly influenced by the immune status of the host as well as by different homeostatic mechanisms [13][14][15][16][17]. In this respect, it has been demonstrated that platelets seem to play a central role in promoting tumoral cells' growth, dissemination and colonization determining the apparition of metastatic deposits, especially through the process of degranulation and the release of proinflammatory cytokines (such as interleukin 6) and Meanwhile, when studying the possible correlation between BRCA status, inflammatory markers and disease-free and overall survival, we observed that BRCA-mutated patients with SII ≥ 841,000 and those with higher NLR values had significantly worse DFS compared to patients with SII < 841,000 and with lower NLR values.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-22 is induced by TLR signaling, and reduces glycolysis/M1 polarization by targeting GLUT1 ( 38 ). Other miRNAs can target other glycolytic genes, such as hexokinase-2, phosphoglucose isomerase, and enolase ( 39 ). In CD4+ T cells, miR-142 regulates the MBD2-MYC axis to promote glycolysis and exacerbate inflammation during myocarditis ( 40 ).…”
Section: Potential Interactions Of Extracellular Vesicles and Immune ...mentioning
confidence: 99%
“…Transfer of metabolites via exosomes can supplement cellular energy production, biosynthesis pathways, and other metabolic processes in recipient cells. Exosomal miRNAs can target specific genes involved in metabolic regulation, thereby altering cellular metabolism in recipient cells [60]. Further research into exosome-mediated metabolic regulation will deepen our understanding of cellular communication and metabolic homeostasis.…”
Section: Alteration In Cell Metabolismmentioning
confidence: 99%